Prevalence and Genetic Analysis of Chromosomal mcr-3/7 in Aeromonas From U.S. Animal-Derived Samples - Wang, Yan; Hou, Naxin; Rasooly, Reuven; Gu, Yongqiang; He, Xiaohua (Frontiers in Microbiology, 2021)
The prevalence of mcr-positive bacteria in 5,169 domestic animal-derived samples collected by USDA Food Safety and Inspection Service between October 2018 and May 2019 was investigated. A procedure including enriched broth culture and real-time PCR targeting mcr-1 to mcr-8 were used for the screening. Fifteen positive isolates were identified, including one plasmid-born mcr-1-positive Escherichia coli strain, EC2492 (reported elsewhere) and 14 mcr-3/7-positive strains from poultry (1), catfish (2) and chicken rinse (11) samples. Analysis of 16S rRNA and whole genome sequences revealed that all 14 strains belonged to Aeromonas. Data from phylogenetic analysis of seven housekeeping genes, including gyrB, rpoD, gyrA, recA, dnaJ, dnaX and atpD, indicated that nine strains belonged to Aeromonas hydrophila and five strains belonged to A. jandaei. Antimicrobial tests showed that almost all mcr-positive strains exhibited high resistance to colistin with MICs ≥ 128mg/L, except for one A. jandaei strain, which showed a borderline resistance with a MIC of 2mg/L. A segment containing two adjacent mcr-3 and mcr-3-like genes was found in two A. hydrophila and one A. jandaei strains and a variety of IS-like elements were found in the flanking regions of this segment. A mcr-3-related lipid A phosphoethanolamine transferase gene was present in all 14 Aeromonas strains, while an additional mcr-7-related lipid A phosphoethanolamine transferase gene was found in 5 A. jandaei strains only. In addition to mcr genes, other antimicrobial resistance genes, including blaOXA-12/OXA-724, aqu-2, tru-1, cepS, cphA, imiH, ceph-A3, ant(3'')-IIa, aac(3)-VIa and sul1 were observed in chromosomes of some Aeromonas strains. The relative high prevalence of chromosome-borne mcr-3/7 genes and the close proximity of various IS elements to these genes highlights the need for continued vigilance to reduce the mobility of these colistin-resistance genes among food animals.